Dark Triad Personality Traits and Selective Hedging - Matthias Pelster; Annette Hofmann; Nina Klocke; Sonja Warkulat (Journal of Business Ethics, 2021)
We study the relationship between risk managers' dark triad personality traits (Machiavellianism, narcissism, and psychopathy) and their selective hedging activities. Using a primary survey of 412 professional risk managers, we find that managers with dark personality traits are more likely to engage in selective hedging than those without. This effect is particularly pronounced for older, male, and less experienced risk managers. The effect is also stronger in smaller firms, less centralized risk management departments, and family-owned firms.
Keywords: G30; G34; G39; 300; Managers; Personality traits; Corporate risk management; Selective hedging